Off to a Good Start Social and Emotional Development of Memphis' Children - Martin, Laurie T. (RAND Corporation, 2014)
Drawing on national, state, and local data, the Urban Child Institute partnered with RAND to explore the social and emotional well-being of children in Memphis and Shelby County, Tenn. The book highlights the importance of factors in the home, child care setting, and community that contribute to social and emotional development.